Controllable S-Vacancies of monolayered Mo–S nanocrystals for highly harvesting lithium storage. (December 2020) - Fan, Linlin; Lei, Shulai; Kheimeh Sari, Hirbod Maleki; Zhong, Longsheng; Kakimov, Alibek; Wang, Jingjing; Chen, Jun; Liu, Dezheng; Huang, Liang; Hu, Junhua; Lin, Liangxu; Li, Xifei
Abstract: Two-dimensional (2D) monolayers are promising in electrochemical energy storages (EES), while their performance is still far below than that can be exploited. Understanding 2D monolayers, particularly thin nanocrystals (NCs) with and without surface modifications in EES would be interesting. This work demonstrates how monolayered molybdenum sulfide (Mo–S) NCs with S vacancies perform as a promising anode material to improve many aspects of lithium-ion batteries (LIBs), by utilizing their metallicity, multi-layer adsorption, minimized self-discharge and fast 2D capacitive processes. By way of examples, we demonstrate an increasing trend of the energy capacity and improved lithium diffusion kinetics associating with the S vacancy and phase change, a discharge capacity of 1409 mAh g −1 at 0.1 A g −1, and even reach the capacitive dominated (>814.7 mAh g −1 ) capacity at 1 A g −1 . It demonstrates that the surface modified Mo–S NCs can be well used in LIBs. There may be also considerable opportunities of similar 2D materials in LIBs and beyond ( e.g. supercapacitor) which can fully exploit the fast 2D capacitive process and high surface capacity. Graphical abstract: Image 1 Highlights: Basic Li + storage behaviors of Mo–S NCs with controlled S-vacancies are explored. Rich surface chemistry of S-depleted Mo–S NCs is beneficial to lithium diffusion kinetics. Metallicity, multi-layer adsorption and fast 2D capacitive processes facilitate capacity improvements.